Analysis of Supporting and Hindering Factors for the Implementation of BIM and GIS Integration in IKN Projects - Fatkhur Rozaq; I putu artama wiguna (Jurnal Indonesia Sosial Teknologi, 2024)
The relocation of Indonesia's capital city from Jakarta to IKN (Capital City of the Archipelago) in Penajam Paser Utara is a monumental project covering an area of 2,876 hectares, which involves massive infrastructure development. To ensure the success of IKN development and development based on the principles in Law Number 3 of 2022 including equality, technological balance, resilience, sustainable development, livability, connectivity, and smart cities. BIM-GIS integration technology was key in managing the complexity of this project. With BIM-GIS integration, it supports digital transformation for more efficient and complete decision-making, including spatial variabels. This thesis aims to analyze the factors that influence the implementation of BIM-GIS integration technology in the early stages of IKN project development. Exploratory factor analysis methods are used to identify supporting factors that facilitate the successful implementation of BIM-GIS integration, as well as inhibiting factors that may hinder it. Questionnaires are used as a data collection tool from stakeholder respondents in IKN projects. Questionnaire data was analyzed using Exploratory Factor Analysis (EFA). The research results showed that there were 16 supporting factors with 4 component groups and 16 inhibiting factors with 6 component groups. Based on these results, strategic steps are proposed to contribute to the development of science and play a role in the successful relocation of Indonesia's capital city.